Sensing Picomolar Concentrations of RNA Using Switchable Plasmonic Chirality. Issue 41 (19th September 2018) - Funck, Timon; Nicoli, Francesca; Kuzyk, Anton; Liedl, Tim
Abstract: Detecting small sequences of RNA in biological samples such as microRNA or viral RNA demands highly sensitive and specific methods. Here, a reconfigurable DNA origami template has been used where a chiral arrangement of gold nanorods on the structure can lead to the generation of strong circular dichroism (CD). Switching of the cross‐like DNA structure is achieved by the addition of nucleic acid sequences, which arrests the structure in one of the possible chiral states by specific molecular recognition. A specific sequence can thus be detected through the resulting changes in the plasmonic CD spectrum. We show the sensitive and selective detection of a target RNA sequence from the hepatitis C virus genome. The RNA binds to a complementary sequence that is part of the lock mechanism, which leads to the formation of a defined state of the plasmonic system with a distinct optical response. With this approach, we were able to detect this specific RNA sequence at concentrations as low as 100 pm . Abstract : A gold–DNA origami template can show strong circular dichroism (CD). Switching of the cross‐like DNA structure is achieved by the addition of nucleic acid sequences, which arrests the structure in one of the possible chiral states by specific molecular recognition. Specific RNA sequences at concentrations as low as 100 pm can be detected through the resulting changes in the plasmonic CD spectrum.